+0  
 
0
209
1
avatar

How to do (25/4*sqrt(3)/(5+2.5sqrt(3)) this step by step?

Guest Sep 20, 2017
edited by Guest  Sep 20, 2017
 #1
avatar+87635 
+1

I'm assuming that you have

 

 (5+2.5sqrt(3))/(25/4*sqrt(3) )   =

 

5 / (25/4*sqrt(3) )    +  2.5sqrt (3) / (25/4 * sqrt (3) )  =

 

5 / (6.25 sqrt (3) )   +  2.5sqrt (3) / ( 6.25 * sqrt (3) )   =

 

5 / (6.25 sqrt (3) )   +  2.5 / ( 6.25  ) 

 

.8 / sqrt (3)   +  .4      =        rationalize the denominator in the frist fraction

 

.8sqrt (3) / [ sqrt (3) * sqrt (3) ]  +   .4  =

 

.8 sqrt (3) / 3  +   .4   =              get a common denominator

 

[.8sqrt (3)  + .4 (3)]  / 3  =

 

 [ .8 sqrt (3)  + 1.2 ]  / 3  =

 

.4 [ 2sqrt (3)  + 3 ]  / 3  =

 

(.4/3) [ 2sqrt (3)  + 3 ]  =

 

(4/30) [ 2sqrt (3) + 3 ] =

 

(2/15) [ 2sqrt (3) + 3  ]  ≈  .861880

 

 

cool cool cool

CPhill  Sep 20, 2017

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.